Worldviews, science and us : bridging knowledge and its implications for our perspectives of the world, proceedings of the workshop on Times of Entanglement, Minsheng Art Museum, Shanghai, 21-22 September 2010 - Aerts, Diederik; Broekaert, Jan; D'Hooghe, Bart (World Scientific, 2011)
The present volume is part of the 'Worldviews, Science and Us' series of proceedings. It contains selected contributions on the subject of bridging knowledge and its implications for our perspectives of the world. This volume also represents the proceedings of the interdisciplinary stream of the international workshop (Part 1) Times of Entanglement, 21-22 September 2010 at the Minsheng Art Museum in Shanghai, People's Republic of China in the context of the Shanghai World Expo 2010 and, related cutting-edge investigations in the quantum paradigm from discussion panels organized by the Leo Apos.